2022
DOI: 10.3389/fpsyg.2022.901412
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate Is Your Correlation? Different Methods Derive Different Results and Different Interpretations

Abstract: Assessing the association between conceptual constructs are at the heart of quantitative research in educational and psychological research. Researchers apply different methods to the data to obtain results about the correlation between a set of variables. However, the question remains, how accurate are the results of the correlation obtained from these methods? Although various considerations should be taken to ensure accurate results, we focus on the types of analysis researchers apply to the data and discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The model fits the data adequately [χ 2 = 5.59, df = 3, p < 0.001, SRMR = 0.04, RMSEA = 0.07, RMSEA Low and Hi 95% CI (0.01, 0.15), CFI = 0.99, TLI = 0.95, IFI = 1.00]. The results of the path model illustrated that the correlation between the predictors was within the acceptable levels (Alamer and Marsh, 2022;Shao et al, 2022). The variance explained by the predictor variables in the outcome variables, i.e., sense of national responsibility, searching for opportunities to volunteer, and the quantity of volunteering made, was 23, 37, and 08%, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…The model fits the data adequately [χ 2 = 5.59, df = 3, p < 0.001, SRMR = 0.04, RMSEA = 0.07, RMSEA Low and Hi 95% CI (0.01, 0.15), CFI = 0.99, TLI = 0.95, IFI = 1.00]. The results of the path model illustrated that the correlation between the predictors was within the acceptable levels (Alamer and Marsh, 2022;Shao et al, 2022). The variance explained by the predictor variables in the outcome variables, i.e., sense of national responsibility, searching for opportunities to volunteer, and the quantity of volunteering made, was 23, 37, and 08%, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…If such misspecified model is assumed, researchers are often obliged to apply data-driven modifications to compensate for ill-fitted models (Alamer, 2022c;Alamer & Marsh, 2022;Alrabai & Alamer, 2022). Nonetheless, procedures such as multiple removal of items and multiple correlation of error terms negatively affect the quality of the internal structure of the models, which consequently provide questionable evidence of the construct validity of the instrument under assessment (Shao et al, 2022). We encourage researchers in metacognitive reading strategies in general to consider composite models in their analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the linear trend analysis of Botes et al (2020) indicated that increased self-perceived FL proficiency resulted in significantly increased FLE [ F (1, 1,617) = 58.867; p < 0.001]. However, the statistical methods adopted in most previous studies, such as correlation and regression analyses, t -tests, and ANOVA, cannot establish causality ( Shao et al, 2022 ). Similarly, the cross-sectional design of studies conducting path analysis made it difficult to determine causality ( Collier, 2020 ), as did the non-experimental design of Dewaele et al (2018) .…”
Section: Literature Reviewmentioning
confidence: 99%